How close are we to hepatitis C virus elimination in Central Europe? - Flisiak, Robert; Frankova, Sona; Grgurevic, Ivica; Hunyady, Bela; Jarcuska, Peter; Kupčinskas, Limas; Makara, Michael; Simonova, Marieta; Sperl, Jan; Tolmane, Ieva; Vince, Adriana; Zarębska-Michaluk, Dorota (Clinical and experimental hepatology, 2020)
AIM OF THE STUDY: To collect and analyse data obtained from HCV opinion leaders/experts from central European countries, on factors which can affect the WHO target of HCV elimination by 2030. MATERIAL AND METHODS: Data were collected from opinion leaders/experts involved in management of HCV infections in Central European countries which participated in 9th Conference of the Central European Hepatologic Collaboration (Warsaw, 10-11 October 2019). A dedicated questionnaire collected current information related to HCV elimination in Bulgaria, Croatia, the Czech Republic, Hungary, Latvia, Lithuania, Poland and Slovakia. RESULTS: The HCV prevalence rate in particular countries varied from 0.2% to 1.7%. In most central European countries all the HCV infected population is eligible for reimbursement of treatment. However, in some countries there are still some limitations related to the stage of the disease and people who inject drugs. All countries have access to at least one pangenotypic regimen. The most common barrier to HCV elimination in all countries is insufficient political will to establish priority for HCV. None of the reporting countries has established a national screening programme. CONCLUSIONS: Access to therapy for HCV is similar and the majority of patients in Central Europe can be treated according to the current guidelines. Unfortunately there are still some limitations and a lack of political will to implement national screening programmes. According to collected data HCV elimination will not be possible in the region by 2030.
Keywords: therapy; epidemiology; liver; hepatitis C virus